1999
DOI: 10.1038/sj.ejcn.1600776
|View full text |Cite
|
Sign up to set email alerts
|

Risk of linear growth retardation during the first two years of life: a new approach

Abstract: The family context exposes children to failure in growth in the first two years of life when there are already stunted children in the household.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Growth retardation due to food rejection may be associated with different factors according to Mitchell, Gorrell, and Greenberg (1980), with nutritional and emotional deprivation as the most important factors. In U.S. studies, 9.6% of infants present with this diagnosis, most of whom are found more often in low-income groups (Lei et al, 1999;Lindberg, Bohlin, & Hagekull, 1991;Tolia, 1995). Other studies comparing children from similar socioeconomic levels have shown that only some home aspects, such as maternal responsiveness, maternal approval of infant behaviors, and organization of physical environment, are associated with growth delay (evaluated by the HOME scale; Casey, Bradley, & Wortham, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Growth retardation due to food rejection may be associated with different factors according to Mitchell, Gorrell, and Greenberg (1980), with nutritional and emotional deprivation as the most important factors. In U.S. studies, 9.6% of infants present with this diagnosis, most of whom are found more often in low-income groups (Lei et al, 1999;Lindberg, Bohlin, & Hagekull, 1991;Tolia, 1995). Other studies comparing children from similar socioeconomic levels have shown that only some home aspects, such as maternal responsiveness, maternal approval of infant behaviors, and organization of physical environment, are associated with growth delay (evaluated by the HOME scale; Casey, Bradley, & Wortham, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…For the BMI model the additional variables with P ≤ 0.20 were maternal poverty index during pregnancy; father’s presence at home during pregnancy and follow-up; having a younger sibling during the study period. Although parity may be a predictor of growth (Prentice et al, 1987) and met the criteria, it was not included as a potential confounder in the full models because it was highly correlated with number of older siblings ( r = 0.95), which showed greater effects in the individual models and has been suggested as an important predictor of early growth (Lawson and Mace, 2008; Lei et al, 1999). …”
Section: Methodsmentioning
confidence: 99%
“…Another factor which conferred a high risk was having a student mother, which may be explained by the resulting reduced family income and individual care and attention given to the child, as he/she has to be left with another carer during the day 31 . The congruence of these findings with previous reports 8,9,32 highlights their relevance to the development of stunting in developing countries.…”
Section: Discussionmentioning
confidence: 99%